Internet Celebrity, Digital Illustration and Tradition: Rethinking Cultural Product Design for the Contemporary Age - You Xuemin; Rafeah Legino (Rekam, 2025)
This study explores the integration of traditional Chinese culture with digital illustration and internet celebrity influence to enhance contemporary promotional strategies. Focusing on the Weibo campaign for the "Ballet Cat" by Great Wall Motors, the research employs a project-based methodology to examine how cultural motifs and celebrity aesthetics can coalesce in effective commercial design. By combining preliminary research, iterative visual development, and audience feedback, the study reveals how culturally informed digital illustrations can foster brand engagement and resonance in an increasingly digital society. Findings underscore the effectiveness of integrating heritage with modern media to shape digital cultural products and inform marketing strategies.